Structure-function relationships of Clostridium difficile toxin A - Craggs, Joanna K. (1999)
Ten overlapping fragments covering the entire Clostridium difficile toxin A gene were cloned and expressed in Escherichia coli. Eight fragments (a', a2, b, c, d, e, f and g) represented the first 5.55kb of the gene whereas two fragments (hl and h2) each spanned the entire C-terminal repeat region of the molecule. All activities relating to binding to carbohydrates (i. e. cold haemagglutination of rabbit erythrocytes), binding to bovine thyroglobulin and non-specific binding to a murine monoclonal antibody were restricted solely to peptides H1 (amino acids [aa] 1834-2683) and H2 (aa 1832-2683). Peptide H2 alone also displayed the ability to bind to cells and to be internalised into endosome-like compartments within the cells. Taken together with the observation that peptide H2 caused a cytopathic effect on Vero cells which was atypical of the holotoxin, these results may indicate that the repeat region of toxin A stimulates intracellular signalling pathways prior to Rho glucosylation. Peptide A2 (aa 1-536) glucosylated recombinant RhoA (rRhoA) in vitro, whereas peptides A'(aa 1-205), B (aa 542-859), C (aa 114-859), D (aa 869-1330), E (aa 542- 1161), G (aa 869-1830) and H2 (aa 1832-2683) did not. The results obtained for peptides A', A2 and C indicate that the first 536 as encompass the catalytic domain for this activity, that more than the first 205 as alone are needed for expression of enzymic activity, and that for a peptide to be active it must not lack the first 113 aa. The first 113 as of the holotoxin are probably essential for the correct folding of the catalytic domain and expression of its activity. These studies were also the first to locate the toxin A ATP binding site to a peptide spanning as 542-859 (peptide B) of the holotoxin. Antibody reaction profiles of antiserum to holotoxin A against toxin A peptides and of antiserum to the peptides against holotoxin A indicate that this region is unexposed in the native state. Also of interest was the observation that the only peptides, which contained the nucleotidebinding site (B and E), lacked the ability to glucosylate rRhoA. Further peptide A2, which possessed glucosyltransferase activity, lacked the nucleotide-binding site. These studies therefore, suggest that a nucleotide-binding site is not required for in vitro glucosylation of rRhoA by toxin A, and fail to identify a role for the toxin A nucleotide binding site. An engineered truncated form of toxin A, consisting of the first 539 as of the holotoxin (encompassing glucosyltransferase activity) fused to the 852 as C-terminal peptide H2 (repeat end binding portion) caused a conventional cytopathic effect (CPE), but was 1,400 fold less cytotoxic to Vero cells than the holotoxin. Peptide A2 (aa 1-536) alone had no effect on Vero cells or in rabbit ileal loops suggesting that peptide H2 aided delivery of the glucosyltransferase molecule into cells leading to a CPE. The truncated toxin lacked the nucleotide binding site and the putative membrane-translocating domain (internal hydrophobic region). The reduced activity of the truncated toxin suggests that although not essential for cytotoxic activity, the nucleotide-binding site and the internal hydrophobic region are important for stability and/or efficient translocation of the holotoxin into the cytosol.